2023
DOI: 10.1155/2023/1631285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Hydrostatic Pressure and Thermal Processing on the Shelf Life and Quality Attributes of Apple-Kiwi-Carrot Puree Blend

Abstract: The effects of high hydrostatic pressure (HHP) (400 MPa/2 min and 500 MPa/2 min) and thermal processing (TP) (90°C/2 min) on the microorganisms, nutrition, color, endogenous enzyme activities, antioxidant capacity, and rheological properties of blended apple-kiwi-carrot puree were comprehensively evaluated after processing and during storage at 4°C. Results showed the microbiological shelf life of the HHP or TP products was at least 24 days. TP inactivated polyphenol oxidase activity more effectively, retainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…When it comes to the application of the aforementioned processing technologies, previous studies from Tian et al (2023) have demonstrated the feasibility of HPP (400 and 500 MPa for 2 min) to extend the shelf-life of an apple-kiwi-carrot puree, as well as to retain some nutritional attributes such as ascorbic acid, total carotenoids, and antioxidant capacity [10]. A study analysing the effects of HPP (600 MPa, 15 min, 48 • C) and US (460 W/cm 2 , 24 kHz, 15 min, 33 ± 7 • C) on strawberry puree was performed by Sulaiman et al (2017) who reported that HPP was better than US to retain antioxidant activity over a period of 30 days at 3 • C, while the later performed better to retain colour [11].…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to the application of the aforementioned processing technologies, previous studies from Tian et al (2023) have demonstrated the feasibility of HPP (400 and 500 MPa for 2 min) to extend the shelf-life of an apple-kiwi-carrot puree, as well as to retain some nutritional attributes such as ascorbic acid, total carotenoids, and antioxidant capacity [10]. A study analysing the effects of HPP (600 MPa, 15 min, 48 • C) and US (460 W/cm 2 , 24 kHz, 15 min, 33 ± 7 • C) on strawberry puree was performed by Sulaiman et al (2017) who reported that HPP was better than US to retain antioxidant activity over a period of 30 days at 3 • C, while the later performed better to retain colour [11].…”
Section: Introductionmentioning
confidence: 99%